Nummular retinal pigment epithelium loss in bilateral diffuse uveal melanocytic proliferation - Neha Goel (Journal of Clinical Ophthalmology and Research)
A rare case of cancer-associated nummular loss of retinal pigment epithelium (RPE) is presented. This subtype of the more commonly reported bilateral diffuse uveal melanocytic proliferation is notable for absence of typical uveal melanocytic proliferation. A 71-year-old male with pancreatic cancer exhibited multiple hypopigmented patches on fundus examination, with corresponding transmission defects on fluorescein angiography and outer retinal and RPE loss on optical coherence tomography, confirming RPE loss as the predominant feature. This was interspersed with zones of preserved RPE which were most prominent on near-infrared reflectance imaging. Recognition of this unusual variant is important to establish an early diagnosis.